DIGITAL CITIZENSHIP IN THE 21ST CENTURY: STRENGTHENING DIGITAL ETHICS - Rahmawati, Dian Eka; Zainudin, Arif; Putri, Aulia (Department of Government, FISIP, Universitas Padjadjaran, 2025)
The concept of digital citizenship in the 21st century, defined as the use of knowledge and skills to behave ethically and responsibly in digital environments. With the rapid development of technology, digital literacy and ethics have become key elements in adapting to the digital world, especially in education, governance, and social participation. This paper also highlights challenges such as the digital divide, authoritarian populism and hate speech, and the need for digital literacy as a solution to mitigate their negative impacts. The purpose of this article is to map previous articles or research on digital citizenship in the 21st century related to the application of digital ethics. Using a qualitative approach, this research analyzed 377 articles obtained from Scopus and visualized with the VOSviewer application. The research found that digital citizenship is growing rapidly, but still faces challenges such as the digital divide, cyberbullying, and lack of digital literacy. In addition, the close link between digital citizenship and digital ethics, particularly in education and social participation, is highlighted. With the integration of evolving technologies, this article emphasizes the importance of strengthening digital ethics and literacy to create an inclusive, safe, and sustainable digital environment, especially amidst the surge in the use of digital platforms.gb777